Performance improvement of supercritical carbon dioxide power cycle at elevated heat sink temperatures. (15th January 2022) - Muhammad, Hafiz Ali; Cho, Junhyun; Cho, Jongjae; Choi, Bongsu; Roh, Chulwoo; Ishfaq, Hafiz Ahmad; Lee, Gilbong; Shin, Hyungki; Baik, Young-Jin; Lee, Beomjoon
Abstract: The supercritical carbon dioxide power cycle has emerged as an advanced power generation system owing to its better efficiency, compactness, and capability to synergize with a broad range of boundary conditions. Its superior performance is due to the liquid-like compression near the critical point. However, this phenomenon deteriorates significantly for elevated heat sink temperatures and is therefore highly detrimental to the cycle performance. Thus, this study proposed and investigated an integrated power and refrigeration cycle scheme to curtail the effects of elevated heat sink temperatures. A theoretical model of the proposed scheme based on industrial flue gases was developed, and the influence of heat sink at a range of heat-source temperatures (200–500 °C) was examined. Subsequently, benchmark cases are established and optimized, and the performance improvement with respect to the benchmark case is reported, with net power as the performance indicator. The optimization of the benchmark case reveals that the simultaneous optimization of low- and high-pressure levels of the cycle is necessary to maximize the net power. The parametric investigation of the proposed configuration shows that the performance is sensitive to the saturation temperature in the evaporator of the refrigeration cycle and to the ratio of low- and high-pressure levels in the power cycle. Therefore, the proposed case was optimized for both influencing parameters for each boundary condition. The results show that for a given heat-source temperature, higher heat sink temperatures favor the proposed design. For the heat-source temperatures of 200 °C, the benchmark case is superior for all heat sink conditions, whereas for 300 °C, 400 °C, and 500 °C, the proposed system results in an increase in power generation of 10.67%, 7.2%, and 5.2%, respectively, at a sink temperature of 50 °C. Finally, a case study with molten salt as the heat source was conducted, and the results indicated that the proposed scheme outperformed the benchmark case by 32.87% in terms of net power. The results are significant in simplifying the design of pressurization components and performance improvement of the supercritical carbon dioxide power cycle at elevated heat sink temperatures. Highlights: The sCO2 power cycle integrated with a refrigeration cycle is proposed. Simultaneous variation of operating pressures enhances performance significantly. The refrigeration cycle is employed to cool CO2 at elevated heat sink temperatures. 10.67% improvement in net power is obtained using integrated scheme.